2019
DOI: 10.1111/mmi.14251
|View full text |Cite
|
Sign up to set email alerts
|

CyaC, a redox‐regulated adenylate cyclase of Sinorhizobium meliloti with a quinone responsive diheme‐B membrane anchor domain

Abstract: Summary The nucleotide cyclase CyaC of Sinorhizobium meliloti is a member of class III adenylate cyclases (AC), a diverse group present in all forms of life. CyaC is membrane‐integral by a hexahelical membrane domain (6TM) with the basic topology of mammalian ACs. The 6TM domain of CyaC contains a tetra‐histidine signature that is universally present in the membrane anchors of bacterial diheme‐B succinate‐quinone oxidoreductases. Heterologous expression of cyaC imparted activity for cAMP formation from ATP to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Since resazurin/resorufin is cell membrane permeable and the presence of resazurin resulted in the downregulation of fumarate reduction, nitrogen reduction, and sulfate reduction genes, resazurin likely entered the periplasm space and interacted with periplasm and inner membrane proteins. As a consequence, resazurin/resorufin may have altered the redox state of inner membrane quinones, and then, the cyclic AMP (cAMP) receptor protein and adenylate cyclase (CyaC) , could respond to the redox change of quinones, finally resulting in the downregulation of the above-mentioned genes. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since resazurin/resorufin is cell membrane permeable and the presence of resazurin resulted in the downregulation of fumarate reduction, nitrogen reduction, and sulfate reduction genes, resazurin likely entered the periplasm space and interacted with periplasm and inner membrane proteins. As a consequence, resazurin/resorufin may have altered the redox state of inner membrane quinones, and then, the cyclic AMP (cAMP) receptor protein and adenylate cyclase (CyaC) , could respond to the redox change of quinones, finally resulting in the downregulation of the above-mentioned genes. , …”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, resazurin/resorufin may have altered the redox state of inner membrane quinones, and then, the cyclic AMP (cAMP) receptor protein 58 and adenylate cyclase (CyaC) 59,60 could respond to the redox change of quinones, finally resulting in the downregulation of the above-mentioned genes. 61,62 In addition, it was previously reported that Mtr gene expression was enhanced in the presence of soluble EMs, such as quinone and flavins. 29 These soluble EMs mainly reacted with outer-membrane proteins (OmcA and MtrC), and consequently, the high demand for electron donors due to the enhanced EET resulted in the upregulation of Mtr genes.…”
Section: Effect Of Resazurin On Current Generation and Biofilm Format...mentioning
confidence: 99%
“…The proteins were cloned in plasmids pUT18, pUT18C, pKT25 and pKNT25 for producing the T18 and T25 fragment for C- and N-terminal fusion, respectively (Klein et al 2023). For the BATCH assays, the bacteria were grown anaerobically in LB broth with 20 mM DMSO which produces highest activities (Wissig et al 2019) in microtiter plates to an OD578 0.6 to 0.9. The β-galactosidase assays (Monzel et al 2023; Wörner et al 2016) were performed as described (Klein et al 2023) and are presented as the mean (with standard deviation) from at least two biological and four technical replicates each.…”
Section: Methodsmentioning
confidence: 99%
“…A different picture emerges regarding associated domains which are not required for activity. In bacterial ACs numerous diverse N-terminal domains have been identified, among them membrane anchors of two, four or six predicted α-helices, and several distinct domains located between membrane anchor and catalytic domain ( Linder and Schultz, 2003 ; Schultz and Natarajan, 2013 ; Beltz et al, 2016 ; Bassler et al, 2018 ; Wissig et al, 2019 ). Thus, each of these bacterial AC isoforms probably is endowed with unique molecular features, which confer peculiar regulatory modalities, almost completely unexplored at this time (for representative samples see Figure 1 and ( Bassler et al, 2018 )).…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting question is why many bacteria contain multiple class III AC isozymes, e.g., 16 in Mycobacterium tuberculosis or 28 in Sinorhizobium meliloti . Notably, the AC CyaC from Sinorhizobium is regulated by its hexahelical membrane domain which contains a di-heme-B entity integrated in its membrane domain enabling regulation by oxidation-reduction processes ( Wissig et al, 2019 ). The regulation of other bacterial ACs with hexahelical membrane domains is unknown.…”
Section: Introductionmentioning
confidence: 99%